Impact of the Food-Labeling and Advertising Law Banning Competitive Food and Beverages in Chilean Public Schools, 2014–2016 - Massri, Camila (Am J Public Health, 2019)
Objectives. To evaluate the impact of a national law banning sales of competitive food and beverages (CF&B) in schools on the availability of CF&B sold at school kiosks. Methods. This study was uncontrolled before and after study. We evaluated public schools in Santiago de Chile (n = 21; 78% response rate) in 2014 and 2016 (6 months after the law came into force). Trained personnel collected data on calories, total sugars, saturated fat, and sodium from food labels. The outcome was the percentage of foods exceeding the cutoff levels defined in the law and the mean difference between 2014 and 2016. Results. Foods exceeding any cutoffs decreased from 90.4% in 2014 to 15.0% in 2016. Solid products had a substantial reduction in calories, sugar, saturated fat, and sodium. Liquid products had a reduction in calories, total sugar, and saturated fat, whereas sodium increased. This was a result of changes in product mix. Conclusions. A ban on sales of CF&B reduced the availability of CF&B at Santiago’s school kiosks. Further research should examine the impact of this ban on food intake and health outcomes.